Mathematical analysis of successive approximation to identify the blood glucose regulation using picards iteration method - Sanchaikumar. N; Swaminathan. B; Muthumani. V; G, Komahan (International Journal of Advanced Mathematical Sciences, 2024)
Diabetes affects millions of peoples all over the world, and the correct identification of Glucose of individuals affected with this disease, especially of those in early stages or in progression towards diabetes, remains an active area of research. This Picard’s Mathematical model is useful to identify the glucose-insulin interactions. In this system we used a couple of ordinary differential equations prevails as an important tool for interpreting data collected during an intravenous glucose tolerance test.(IVGTT). In this study we extract the solution to the Picard’s method and for identifying patient-specific parameters of glucose trajectories form IVGTT. As illustrated with patient data, our approach seems to have an edge over nearly an accurate approximate value using this method. Additionally, we also present an application of our method to prediction of the time to baseline glucose and calculation of glucose effectively, two quantities regarded as significant in diabetes diagnostics.